2019
DOI: 10.1007/s00520-019-04816-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of anticoagulation in patients with metastatic castration–resistant prostate cancer receiving abiraterone + prednisone

Abstract: Monitor INR 3 days after initiation and then once weekly for 4 weeks, as INR becomes stable the interval may increased slowly.Figure 1.0. Anticoagulation management for atrial fibrillation in a patient receiving abiraterone + prednisone. Abbreviations: CAD; coronary artery disease. ASA; acetylsalicylic acid. CHADS 2 ; congestive heart failure, hypertension, age >65, diabetes, prior stroke or transient attack. CrCl; creatinine clearance. INR; international normalized ratio. * -Close monitoring of INR Abbreviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The vast majority of scientific research concerns patients with hormone- and chemotherapy. [ 27 , 32 , 33 , 34 ]. Significant impact on risk factors has the presents of metastases.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of scientific research concerns patients with hormone- and chemotherapy. [ 27 , 32 , 33 , 34 ]. Significant impact on risk factors has the presents of metastases.…”
Section: Resultsmentioning
confidence: 99%
“…The IDS varied in a wide range and after dichotomization the high IDS proved to predict a significantly longer AA treatment and OS compared to the low IDS. In case of patients treated with AA, the IDS is a mirror of DDI, which was the main subject of some reports ( Graff and Beer, 2014 ; Benoist et al, 2016 ; Jamani et al, 2016 ; Bonnet et al, 2017 ; Del Re et al, 2017 ; Dubinsky et al, 2019 ; Escudero-Vilaplana et al, 2020 ; Vicente-Valor et al, 2021 ). However, none of these studies analyzed the impact of DDI on the outcome of AA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of tamsulosin and tramadol in our case has been described above, while the frequency of duloxetine was 1%. The other publications ( Graff and Beer, 2014 ; Benoist et al, 2016 ; Del Re et al, 2017 ; Dubinsky et al, 2019 ) evaluated the potential DDI based on theoretical considerations from the literature. A list of drugs was given with different grades of DDI ( Del Re et al, 2017 ) (drugs not present in our study are in italics and the DS is indicated for other drugs): increased DDI [amiodarone (DS = 23), flecainide , hydrocodone and propafenone (13)] or moderate (amitriptyline (16), aripiprazole , carbamazepine (−5), carvedilol (8), codeine (2.5), donepezil , duloxetine (13), fluoxetine , fosamprenavir , galantamine , metoprolol (7), mexiletine , nicardipine , oxycodone (5), pioglitazone , propranolol , paroxetine (16), pimozide , risperidone , ritonavir , trazodone and venlafaxine (8)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation